Analisis Kandungan Material Campuran Aspal Panas Mix Design AC-WC terhadap Rekonstruksi Jalan Ruas N-029.1 Bts. Kab. Muaro Jambi / Kab. Tanjabtim-Bts. Kab. Tanjabbar - Ayzadt, Muhammad; Nurdin, Ade; Bahar, Fetty Febriasti (Universitas Batanghari Jambi, 2024)
To obtain a good aggregate mixture, efforts are made to keep the gradation of the aggregate mixture in the middle of its specification range. Based on road reconstruction work on section N-029.1 Bts. Regency. Muaro Jambi / Kab. Tanjabtim – Bts. Regency. Tanjabbar is at the point (sta 16+000 – 16+400) where the asphalt that is spread has a soft/liquid texture, which can be seen from the process of compacting and leveling the asphalt layer which is carried out by operating with a number of passes that is not in accordance with what was planned during the trial mix. So it is necessary to carry out an analysis to evaluate the material composition of the hot mix asphalt design layered by Asphalt Concrete-Wearing Course (AC-WC). The method used is to use secondary data analysis methods in the form of DMF, JMF and gradation data. The results of the analysis of the composition of the hot asphalt mix material show that there are differences in the total proportion value of the mixture, where in the DMF the planned proportion is 32.97% for fine aggregate, 28.26% for medium aggregate, 18.84% for coarse aggregate, 1.88 % for filler, and 5.80% for asphalt. At JMF the proportion of results from weighing is 37.68% for Hot Bin I (fine aggregate), 35.80% for Hot Bin II (medium aggregate), 18.84% for Hot Bin III (coarse aggregate), 1.88% for filler, and 5.80% for asphalt. In field implementation, the proportion of the total mixture produced was 17.90% for Hot Bin III (coarse aggregate), 33.91% for Hot Bin II (medium aggregate), 40.51% for Hot Bin I (fine aggregate), 1, 88% for filler, and 5.81% for asphalt.